Implementasi Gerakan Literasi Sekolah (GLS) pada Keterampilan Membaca Siswa Kelas III SDN 1 Jatigunung - Cahyani , Regita; Ardhyantama, Vit; Aristya, Ferry (Scholarly Journal of Elementary School, 2022)
This study aims to (1) describe the implementation of the school literacy movement at SDN 1 Jatigunung for the 2019/2020 academic year, (2) determine students' reading skills through the implementation of the school literacy movement at SDN 1 Jatigunung for the 2019/2020 academic year, ( 3) find out the obstacles and solutions in the implementation of the school literacy movement. This research applied qualitative descriptive method. The subjects of this study were 1 school principal, 1 teacher, 33 students, and 2 parents of SDN 1 Jatigunung students. Student and parent subjects were selected by purposive sampling. Data collection techniques include documentation and observation of GLS implementation, and interviews. The results obtained in this study are: 1) The implementation of the school literacy movement at SDN 1 Jatigunung was good. The teacher has implemented 3 stages, namely: habituation, development, and learning; 2) students' reading skills, especially in grade III 70%, were fluent in reading. Through the school literacy movement, teachers have invited their students to always get used to reading. And for students who still have difficulty in reading, the teacher makes slow reading service program; 3) An obstacle in the implementation of the school literacy movement is the lack of supply of book collections in the library so that schools are trying to use BOS to help increase the collection of library books.